2018
DOI: 10.1039/c8cy00143j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photocatalytic activity of BiOBr nanosheets with tunable crystal facets and sizes

Abstract: A series of BiOBr nanosheets with tunable exposed facets and crystallite sizes were prepared via a solvent adjustment strategy. The exposed facet and thickness of BiOBr nanosheets are both important for their photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In order to boost the photocatalytic performance, there are adopted various strategies such as heterostructure, crystal facet exposure, doping, the engineered defects, dimension tuning, etc. [6][7][8][9][10][11][12]. Recently, Wang et al demonstrated that excitons could be effectively dissociated into charge carriers with the incorporation of oxygen vacancy, leading to excellent performances in superoxide generation and selective organic syntheses under visible-light illumination [13].…”
Section: Introductionmentioning
confidence: 99%
“…In order to boost the photocatalytic performance, there are adopted various strategies such as heterostructure, crystal facet exposure, doping, the engineered defects, dimension tuning, etc. [6][7][8][9][10][11][12]. Recently, Wang et al demonstrated that excitons could be effectively dissociated into charge carriers with the incorporation of oxygen vacancy, leading to excellent performances in superoxide generation and selective organic syntheses under visible-light illumination [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the small thickness (50 nm) obtained for the B-1:3 by using the deionized water/absolute methanol volume ratio (1 : 3) can shorten the transfer distance of photoinduced e À -h + pairs from the interior to the surface of photocatalyst, leading to the efficient separation of e À -h + pairs and contributes to the excellent photoactivity. 34 Impressively, degradation efficiency of the B-1:3 is far superior to that of reported BiOBr and modied BiOBr photocatalysts in the literature (Table S1 †). To analyze the reaction kinetics of RhB degradation for BiOBr materials, the data was tted according to the simplied Langmuir-Hinshelwood model: 46 and the result is presented in Fig.…”
Section: Optical and Photoelectrical Propertiesmentioning
confidence: 82%
“… 29 BiOBr nanosheets were synthesized by a facile solvothermal route in a mixed solvent of n -propanol, water and acetic acid, and displayed enhanced photodegradation performance of salicylic acid and RhB due to exposed (001) facet and small thickness. 34 0D/1D g-C 3 N 4 homojunction was synthesized by a hydrothermal route and displayed enhanced photodegradation performance of RhB, which is attributed to enhanced separation efficiency of carriers. 35 Hence, it is highly meaningful to design highly efficient BiOBr photocatalyst by constructing the microstructure using a facile method for realizing the practical application.…”
Section: Introductionmentioning
confidence: 99%
“…When hydrothermally synthesized, BiOBr appear as nano-sheets which are optically transparent due to their bandgap at 2.76 eV (449 nm). [35] Scanning electron microscopy reveals that such nanosheets with lateral extents between 0.25 and 2 µm cover the whole surface of the Cs 3 Bi 2 Br 3 I 6 wafer (Figure 2D and Figure S4A, Supporting Information). Before annealing, the sample-surface was completely free of such nanosheets (Figure S4B, Supporting Information), proving that the annealing step also possibly results in a passivation in the case of the Cs 3 Bi 2 Br 3 I 6 .…”
Section: Cs 3 Bi 2 Br 3 I 6 Wafers and Their Passivationmentioning
confidence: 99%